Antithrombotic therapy trends in non-valvular atrial fibrillation patients undergoing percutaneous coronary stent implantation: Results from a survey among fellows at the Japanese College of Cardiology. Issue 2 (August 2018) - Fukamachi, Daisuke; Hirayama, Atsushi; Miyauchi, Katsumi; Yasuda, Satoshi; Ogawa, Hisao; Ito, Hiroshi; Daida, Hiroyuki
Highlights: Antithrombotic therapies prescribed vary widely among cardiologists. We conducted a questionnaire based survey for antithrombotic therapy prescribed. Variation exists in antithrombotic therapy for oral anticoagulants-treated atrial fibrillation patients after stenting. Duration of dual antiplatelet therapy tended to shorten. Abstract: Background: Antithrombotic therapy with oral anticoagulants (OAC) in patients with atrial fibrillation (AF) after stent implantation, where dual antiplatelet therapy (DAPT) is also recommended, is not established. Antithrombotic therapies prescribed vary widely among cardiologists and may change year by year, according to the accumulation of new evidence. Methods: A questionnaire-based survey concerning the antithrombotic therapy prescribed for OAC-treated AF patients who underwent stent implantation was conducted from 2014 to 2016. The survey was completed by the Fellows of the Japanese College of Cardiology (FJCC). Results: The questionnaire was sent to 1023 fellows in 2014, a total of 1057 fellows in 2015, and 1073 fellows in 2016; 268 (26%), 418 (40%), and 416 (39%) answers were obtained, respectively. The duration of DAPT did not change in patients with bare metal stents; however, it tended to become shorter with the use of the drug-eluting stent (DES). Significant shortening of DAPT duration was observed with DES for stable coronary artery disease from 2015 to 2016. A similar tendency was observed for acute coronary syndrome (ACS); however, this was not significant between 2015 and 2016. A shorter duration of DAPT is preferred by electrophysiologists rather than by interventionalists and general cardiologists. OAC monotherapy is not popular one year after stent implantation, although the prevalence of its use increased year by year. Aspirin and thienopyridines are used equally as a single antiplatelet in DAPT, and clopidogrel is also a popular agent. The prevalence of direct OAC use increased year by year. Conclusions: The questionnaire showed variation in antithrombotic therapy used for OAC-treated AF patients after stenting, and how it changes year by year. Although the duration of DAPT tended to shorten, variations are still observed, i.e. the selection of a single antiplatelet or OAC.